مستوى المهارات القيادية السلوكية لدي قائد المؤسسة من وجهة نظر العمال - بونجار ،نادية; كربوش، هشام (جامعة الوادي University of Eloued, 2025)
This study aimed to measure the level of behavioral skills of the manager of the industrial and commercial group of Moulins d'Auras in Batna from the point of view of the workers and to discover the existence of statistically significant differences between the opinions of the workers according to: certain variables (gender, level of education, experience). The study was applied to a random sample of about 50 employees. The descriptive analytical approach was used, in addition to a questionnaire composed of 10 dimensions, as follows : (effective communication, decision making, conflict management, motivation, justice and fairness, adaptability, emotional intelligence, relationship building, delegation effectiveness, creativity, and innovation), each dimension contains four items. The results of the study showed that the manager practices behavioral leadership skills to an acceptable degree from the point of view of employees, with statistically significant differences in the opinions of employees attributed to the variables (gender, university degree, professional experience).
The level of behavioral leadership skills of the institution’s leader from the workers’ point of view: a field study at the industrial and commercial complex, Awras Mills, Batna
Keywords: المهارات; القيادة; السلوك; المؤسسة; العمال; The company; Employee; leadership; Behavior; Skills.